RagC phosphorylation autoregulates mTOR complex 1. (14th December 2018) - Yang, Guang; Humphrey, Sean J; Murashige, Danielle S; Francis, Deanne; Wang, Qiao‐Ping; Cooke, Kristen C; Neely, G Gregory; James, David E
Abstract: The mechanistic (or mammalian) target of rapamycin complex 1 (mTORC1) controls cell growth, proliferation, and metabolism in response to diverse stimuli. Two major parallel pathways are implicated in mTORC1 regulation including a growth factor‐responsive pathway mediated via TSC2/Rheb and an amino acid‐responsive pathway mediated via the Rag GTPases. Here, we identify and characterize three highly conserved growth factor‐responsive phosphorylation sites on RagC, a component of the Rag heterodimer, implicating cross talk between amino acid and growth factor‐mediated regulation of mTORC1. We find that RagC phosphorylation is associated with destabilization of mTORC1 and is essential for both growth factor and amino acid‐induced mTORC1 activation. Functionally, RagC phosphorylation suppresses starvation‐induced autophagy, and genetic studies in Drosophila reveal that RagC phosphorylation plays an essential role in regulation of cell growth. Finally, we identify mTORC1 as the upstream kinase of RagC on S21. Our data highlight the importance of RagC phosphorylation in its function and identify a previously unappreciated auto‐regulatory mechanism of mTORC1 activity. Synopsis: The mechanistic target of rapamycin complex1 (mTORC1) controls cell growth, proliferation and metabolism in response to diverse stimuli. This study identifies a new auto‐regulatory branch of mTORC1 signaling involving phosphorylation of the Rag GTPase RagC by mTORC1, which is required for full mTORC1 activation by growth factors and amino acids. Growth factors and amino acids stimulate mTORC1‐mediated phosphorylation of RagC. RagC phosphorylation is essential for both growth factor‐ and amino acid‐induced mTORC1 activity. RagC phosphorylation is required for mTORC1 regulation of cell size and autophagy in vitro and in Drosophila wing discs. RagC phosphorylation is associated with activation and concomitant destabilization of mTORC1. Abstract : Growth factor‐responsive phosphorylation of the amino acid‐responsive Rag GTPase exemplifies a new interplay between the two parallel main pathways of mTORC1 regulation.